Detection of inflammatory bowel disease in adults and children: evaluation of a new isotopic technique. Issue 6504 (2nd November 1985) - Dawson, D J; Khan, A N; Miller, V; Ratcliffe, J F; Shreeve, D R
Abstract : The distribution of radioactivity after the oral administration of sucralfate labelled with technetium-99m was studied in 33 patients with Crohn's disease (13 adults, 20 children), 10 with ulcerative colitis (four adults), and 29 controls (23 with upper intestinal disease, four irritable bowel, one hypolactasia, and one malrotation of the gut). Positive scans were obtained in all patients with ulcerative colitis and 29 of 31 with active Crohn's disease. The scans of two patients with inactive Crohn's disease were negative. There were two false negative scans in patients with Crohn's colitis and one false positive scan. Overall, sensitivity was 95% and specificity 97%. Comparison with radiology in 39 patients showed similar distribution of disease in 24 and more extensive disease in 12. The scan was inexpensive, simple to perform, well tolerated, allowed small and large bowel to be visualised simultaneously, and used a lower dose of radiation than barium studies. It may prove useful as a screening test for inflammatory bowel disease and in the serial assessment of disease activity.